Impact of a large artificial lake on regional climate: A typical meteorological year Meso-NH simulation results - Iakunin, Maksim (2021)
Large artificial lakes and reservoirs affect the meteorological regime of the shore area and the local climate takes on a number of new features that were previously absent. This work focuses on the weather impact of the Alqueva reservoir, the largest artificial lake in Western Europe. An extensive set of numerical simulations using Meso-NH mesoscale atmospheric model coupled with FLake (Freshwater Lake) scheme was carried out. The simulations cov- ered a 12-month period that was chosen to compose a so-called Typical Meteo- rological Year. This artificial time period is meant to represent the typical meteorological conditions in the region and the model results are used to assess the changes in the local climate. To evaluate the raw impact of the reser- voir, two different scenarios of simulations were compared: (A) with the reser- voir as it exists nowadays and (B) without the reservoir using the older surface dataset. The results show decrease of air temperature during daytime (10–9 ºC) and nighttime increase (up to 10 ºC). In nearest towns, daily maximum temper- ature decreased and daily minimum temperature increased, which refers to milder weather conditions. Alqueva mainly showed suppression in fog forma- tion in the nearby area. Local breeze regime was studied and monthly lake/ land breezes were described.